Transcription analysis of neonicotinoid resistance in Mediterranean (MED) populations of B. tabaci reveal novel cytochrome P450s, but no nAChR mutations associated with the phenotype. (December 2015) - Ilias, Aris; Lagnel, Jacques; Kapantaidaki, Despoina E.; Roditakis, Emmanouil; Tsigenopoulos, Costas S.; Vontas, John; Tsagkarakou, Anastasia
Abstract Background Bemisia tabaci is one of the most damaging agricultural pests world-wide. Although its control is based on insecticides, B. tabaci has developed resistance against almost all classes of insecticides, including neonicotinoids. Results We employed an RNA-seq approach to generate genome wide expression data and identify genes associated with neonicotinoid resistance in Mediterranean (MED)B. tabaci (Q1 biotype). Twelve libraries from insecticide resistant and susceptible whitefly populations were sequenced on an Illumina Next-generation sequencing platform, and genomic sequence information of approximately 73 Gbp was generated. A reference transcriptome was built byde novo assembly and functionally annotated. A total of 146 P450s, 18 GSTs and 23 CCEs enzymes (unigenes) potentially involved in the detoxification of xenobiotics were identified, along with 78 contigs encoding putative target proteins of six different insecticide classes. Ten unigenes encoding nicotinic Acetylcholine Receptors (nAChR), the target of neoinicotinoids, were identified and phylogenetically classified. No nAChR polymorphism potentially related with the resistant phenotypes, was observed among the studied strains. DE analysis revealed that among the 550 differentially (logFC > 1) over-transcribed unigenes, 52 detoxification enzymes were over expressed including unigenes with orthologues in P450s, GSTs, CCE and UDP-glucuronosyltransferases. Eight P450 unigenes belonging to clades CYP2, CYP3 and CYP4 were highly up-regulated (logFC > 2) including CYP6CM1, a gene already known to confer imidacloprid resistance inB. tabaci . Using quantitative qPCRs, a larger screening of field MEDB. tabaci from Crete with known neonicotinoid phenotype was performed to associate expression levels of P450s with resistance levels. Expression levels of five P450s, including CYP6CM1, were found associated with neonicotinoid resistance. However, a significant correlation was found only in CYP303 and CYP6CX3, with imidacloprid and acetamiprid respectively. Conclusion Our work has generated new toxicological data and genomic resources which will significantly enrich the available dataset and substantially facilitate the molecular studies in MEDB. tabaci . No evidence of target site neonicotinoid resistance has been found. Eight P450 unigenes, including CYP6CM1, were found significantly over-expressed in resistantB. tabaci . This study suggests at least two novel P450s (CYP303 and CYP6CX3) as candidates for their functional characterization as detoxification mechanisms of neonicotinoid resistance inB. tabaci.